Aroma yang Menyentuh Hati: Analisis Pengaruh Persepsi Kualitas Produk terhadap Loyalitas Pelanggan Parfum Fres & Natural - Teti Sumarni; Harto, Budi; Prima Vandayani; Mira Kharisma (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2024)
Companies not only need to make high-quality products in the era of globalization and increasingly fierce competition, but also need to know how consumers' perception of product quality affects their decision to remain loyal to the brand. This is especially true for local brands such as Fres & Natural, where consumer perception of product quality is crucial to building a loyal customer base, especially those who live in the area. In the perfume industry, this study found that many people do not know about how perceived product quality affects customer loyalty. The results of the analysis show that positive perceptions of product quality, such as aroma, durability, and packaging design, have a significant effect on customer loyalty. This study uses a descriptive correlational method with data collection through a Likert scale-based questionnaire. In addition, consumers who are satisfied with product quality tend to buy the product again and suggest others to buy. The results suggest that companies should continue to improve product quality and conduct regular brand performance evaluations to maintain customer loyalty.